4+10(-2x+3)=-66

Simple and best practice solution for 4+10(-2x+3)=-66 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4+10(-2x+3)=-66 equation:


Simplifying
4 + 10(-2x + 3) = -66

Reorder the terms:
4 + 10(3 + -2x) = -66
4 + (3 * 10 + -2x * 10) = -66
4 + (30 + -20x) = -66

Combine like terms: 4 + 30 = 34
34 + -20x = -66

Solving
34 + -20x = -66

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-34' to each side of the equation.
34 + -34 + -20x = -66 + -34

Combine like terms: 34 + -34 = 0
0 + -20x = -66 + -34
-20x = -66 + -34

Combine like terms: -66 + -34 = -100
-20x = -100

Divide each side by '-20'.
x = 5

Simplifying
x = 5

See similar equations:

| X=0.08-0.8 | | (x*x)+25x-60=0 | | x+18=6-2x | | -1(-5n)=-7n+3 | | 8x-14+6x-25= | | -1-5n=-7n+3 | | x=2(x^1/2) | | 2.00=(6.00)(8.00)/X | | x=2x^1/2 | | -7x/-1 | | 4.00=(6.00)(8.00)/X | | 5(2x-15)-3x=-124 | | 2x+2(-5x+18)=116 | | x+2-6x=-5.5 | | -14-25= | | 8-4p=1p+13 | | g(t)=-16t^2+100t+7 | | -2cos^2x+cosx=0 | | 3x+2y=7.25 | | 2x+3(2x-12)=36 | | 8y^2x^2=512 | | 2y-x=8x-2 | | 5y^2x^2=125 | | Y=5(-2)-7 | | 2y-3+xy+3x=5 | | 9xy+9xy= | | 3xy-x+9y+2=0 | | 4x^2+8x-4=100 | | log(10)x=0.6 | | -3x^2=-7x+12 | | 3x*y-x+9y+3=13 | | 3.1x-4=2.1x |

Equations solver categories